Blood and body fluids exposure, post-exposure prophylaxis, and HIV self-testing among healthcare workers in northern Nigeria - Zubairu Iliyasu; Musa Babashani; Khadija Dantata; Shaheed A. Zakariyyah; Muktar A. Gadanya; Humayra A. Bashir; Auwalu U. Gajida; Muktar H. Aliyu (HIV Research & Clinical Practice)
Introduction In high-HIV burden settings, such as Nigeria, HIV self-testing and post-exposure prophylaxis (PEP) are often recommended, but not widely practiced. This study aims to identify the predictors of PEP utilization and preferences for HIV self-testing among healthcare workers in Nigeria. Methods A total of 403 healthcare workers from a tertiary hospital in Nigeria completed questionnaires. Adjusted odds ratios were derived from logistic regression models. Results Among the respondents, 141 (35.0%) reported experiencing at least one workplace exposure incident, with 72 (51.1%) of them receiving PEP. The majority of healthcare workers (n = 354, 87.8%) expressed a preference for HIV self-testing over traditional HIV testing and counseling. The occurrence of exposure incidents was predicted by the respondent’s sex (adjusted odds ratio [aOR] = 1.25; 95% confidence interval [CI]: 1.15-3.08, female vs. male), age (aOR = 0. 16; 95% CI: 0.03-0.92, >40 vs. <30 years), profession (aOR = 1.88; 95% CI: 1.18-4.66, nurse/midwife vs. physician), work unit (aOR = 0.06; 95% CI: 0.02-0.23, obstetrics/gynecology vs. surgery), and previous HIV testing and counseling (aOR = 0.01; 95% Cl: 0.004-0.03, no vs. yes). Respondent’s profession, work unit, and previous HIV testing and counseling independently predicted a preference for HIV self-testing. Conclusion Further exploration of the feasibility of implementing HIV self-testing as an alternative to traditional HIV testing and counseling for workplace exposures is warranted.